Usefulness of radiological findings for predicting cochlear implantation outcomes in children with cochlear nerve deficiency: a pilot study. (2nd October 2016) - Chao, Xiuhua; Luo, Jianfen; Fan, Zhaomin; Shi, Honglu; Han, Yuechen; Wang, Ruijie; Song, Yujie; Wang, Guangbin; Wang, Haibo; Xu, Lei
Abstract: Conclusion: Children with CND received limited benefits from CIs and their results varied. The size of the vestibulocochlear nerve relative to the facial nerve could potentially be used as a predicator for CI outcomes in children with CND. Objective: This study aimed to (1) retrospectively review the outcomes of cochlear implants (CIs) in children with cochlear nerve deficiency (CND) and (2) evaluate the clinical usefulness of radiological findings as predictors for post-implantation outcomes. Methods: Study participants included 10 children with bilateral CND and profound sensorineural hearing loss. The preoperative magnetic resonance imaging and temporal bone computed tomography scans were evaluated. Auditory processing capability and speech perception performance were measured with Categories of Auditory Performance (CAP) and Speech Intelligibility Rating (SIR) scales. Aided hearing thresholds with CI were measured. The relationships between CI outcomes and the sizes of vestibulocochlear nerve and cochlear nerve canal (CNC) were analysed. Results: Although post-operative CAP scores and hearing thresholds significantly improved in children with CND, their results were worse than those measured in implanted children with normal cochlear nerve. No significant correlation was found between the CI outcomes and the vestibulocochlear nerve diameters or the CNC diameters in children with CND. However, children with larger vestibulocochlear-nerve-to-facial-nerve-ratios got better results.